Tax Measures to Support Russian Business in The Context of a Pandemic ("Journal "U". Economy. Management. Finance.", 2021)
This article presents the main tax measures to support small and medium-sized businesses in Russia, which these subjects have received and continue to receive in the context of the development and spread of the new coronavirus infection Covid-19. The study also assessed income tax revenues to the consolidated state budget in 2018-2020, and noted a tendency to reduce these revenues in 2020 during the development of the pandemic. Conclusions were drawn about the importance of small and medium-sized businesses for the Russian economy as a whole and for the population in particular, as well as about the role of tax measures to support these business entities in order to help stabilize the economic situation.
Keywords: taxation; small business; medium business; USN; PSN; UTII; covid-19